2016
DOI: 10.1016/j.anaerobe.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic efficacy of 405 nm light and chlorinated disinfectants for the enhanced decontamination of Clostridium difficile spores

Abstract: The ability of Clostridium difficile to form highly resilient spores which can survive in the environment for prolonged periods causes major contamination problems. Antimicrobial 405nm light is being developed for environmental decontamination within hospitals, however further information relating to its sporicidal efficacy is required. This study aims to establish the efficacy of 405nm light for inactivation of C. difficile vegetative cells and spores, and to establish whether spore susceptibility can be enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Yet, this appeared to be an organism-specific phenomenon, as another Gram-negative pathogen, P. aeruginosa, displayed the greatest susceptibility as measured by reduction in cell viability of the bacterial species tested. Similarly, S. aureus exhibited appreciable 405 nm decolonization properties suggesting that the technology may be applicable to decolonizing hospital associated surfaces and warrant future studies aimed at comprehensively understanding the spectrum of susceptible species, dosing powers, and the recently recognized synergistic potential of 405 nm light in combination with chemical disinfectants [39]. We also measured the LDF system's performance toward planktonic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, this appeared to be an organism-specific phenomenon, as another Gram-negative pathogen, P. aeruginosa, displayed the greatest susceptibility as measured by reduction in cell viability of the bacterial species tested. Similarly, S. aureus exhibited appreciable 405 nm decolonization properties suggesting that the technology may be applicable to decolonizing hospital associated surfaces and warrant future studies aimed at comprehensively understanding the spectrum of susceptible species, dosing powers, and the recently recognized synergistic potential of 405 nm light in combination with chemical disinfectants [39]. We also measured the LDF system's performance toward planktonic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Moorhead et al established the efficacy of the combination therapy of aBL with low concentration chlorinated disinfectants for enhanced inactivation of C. difficile spores (Moorhead et al, 2016a). C. difficile spores suspended in the hospital disinfectants sodium hypochlorite, Actichlor or Tristel at non-lethal concentrations were exposed to aBL at 405 nm.…”
Section: Synergism Of Antimicrobial Blue Light With Other Agentsmentioning
confidence: 99%
“…For example, Haughton et al (2012) inactivated Campylobacter jejuni using 395 nm light, while Bumah et al (14,15) demonstrated the antimicrobial efficacy of 470 nm light against Salmonella enterica and S. aureus. Additionally, a small number of bacterial endospores, fungi and yeasts have been inactivated using violet-blue light (16)(17)(18)(19)(20)(21)(22)(23). To date, little is known about viral susceptibility; however, there is now published evidence demonstrating 405 nm light inactivation of a viral surrogate, bacteriophage ɸC31, and a mammalian virus, feline calicivirus, without the requirement of additional photosensitizers (24,25).…”
Section: Introductionmentioning
confidence: 99%